2020
DOI: 10.1038/s41598-020-70492-2
|View full text |Cite|
|
Sign up to set email alerts
|

Salmonella enterica serovar Typhi exposure elicits ex vivo cell-type-specific epigenetic changes in human gut cells

Abstract: Salmonella enterica serovar Typhi ( S . Typhi) causes substantial morbidity and mortality worldwide, particularly among young children. Humans develop an array of mucosal immune responses following S . Typhi infection. Whereas the cellular mechanisms involved in S . Typhi infection have been intensively studied, very little is known about the early chromatin modifications occurring in the human gut microenvironment that influence d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Several outstanding questions remain regarding the mechanism (s) of transcriptional and post-transcriptional regulation of HLA-G expression on MAIT cells. After S. Typhi exposure, MAIT cells undergo multiple coordinated modifications on Arg-me2(asy) and H4K20me3, H3K4me3, H4K20me1 epigenetic marks (47). Thus, epigenetic changes might be important in underlying these responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several outstanding questions remain regarding the mechanism (s) of transcriptional and post-transcriptional regulation of HLA-G expression on MAIT cells. After S. Typhi exposure, MAIT cells undergo multiple coordinated modifications on Arg-me2(asy) and H4K20me3, H3K4me3, H4K20me1 epigenetic marks (47). Thus, epigenetic changes might be important in underlying these responses.…”
Section: Discussionmentioning
confidence: 99%
“…Mass cytometry assays were performed as previously described with small modifications (47). Briefly, CD45-stained-B-LCL cells were co-cultured with PBMC containing MAIT cells in the presence of mAbs to CD107a and CD107b (15 ml of each/1 x 10 6 cells in 500 ml of R10 medium).…”
Section: Mass Cytometrymentioning
confidence: 99%
“…To visualise the variance of 15 possible FCOM T-cell phenotypes, we performed principal component analysis (PCA) as described previously with small modifications. 56 Briefly, the calculation of principal components was performed by ClustVis web tools. 57 Columns were grouped using correlation distance (Pearson correlation subtracted from 1) and average linkages calculated.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported the impact of Salmonella infection on the early chromatin modifications occurring in the human gut microenvironment, which influence downstream immune responses in epithelial cells and immune cells [85] . S .…”
Section: Microbial Post-translational Modifications and Carcinogenesismentioning
confidence: 99%
“…[84] A recent study reported the impact of Salmonella infection on the early chromatin modifications occurring in the human gut microenvironment, which influence downstream immune responses in epithelial cells and immune cells. [85] S. Typhi-induced PTMs in histone methylation and acetylation associated with epithelial cells, natural killer T, mucosal-associated invariant T, T cell receptor-gd, monocytes, and CD8+ T-cells that are related to both gene activation and silencing. It found that arginine methylation might regulate the early differentiation of effector-memory CD4+ T-cells following exposure to S. Typhi.…”
Section: Microbial Post-translational Modifications and Carcinogenesismentioning
confidence: 99%